Деякі питання профілактики психосоматичних захворювань серед плавскладу у рейсі - Коваль, О.О.; Журавльова, О.М.; Рибак, І.Т. (Актуальні проблеми транспортної медицини, 2005)
The authors have considered some questions of psychosomatic diseases prophylaxis among seafarers under the conditions of a sea voyage. They describe the factors affecting significantly seafarers' nervous activity, including nervous and psychic sphera. They have shown the necessity to work out a prophylactic complex programm and highlighted several points this programm should be directed to.